Development of Video Learning Media Based on Robert Gagne's Theory (Nine Events of Instruction) in Informatics Subjects at Junior High School - Sri Mulyani; Darmansyah Darmansyah; Zelhendri Zen; Fetri Yeni J (Postgraduate, University of Mataram, 2024)
One component that cannot be separated from the learning process is learning media. Learning media is an essential part of education, regardless of the curriculum, because it plays a crucial role in influencing the quality and success of learning. The Informatics subject is no exception, as it introduces computers to students. This introduction is the initial stage of informatics lessons. In presenting the learning process through computer application materials, good preparation is essential. An educator should do more than just coordinate students in front of the computer, use a loud voice to direct them, or write notes on the blackboard. They must wisely package the teaching materials to make learning enjoyable, allowing students to feel that the classroom is a place to explore while they learn to use a computer. This type of research is development and research (R&D) using the ADDIE model. Product validation tests were conducted by three validators: one material validator, one language validator, and one media validator. The product trial involved 30 seventh-grade students from SMPN 1 Siak Hulu, aimed at assessing the practicality of the developed product. The effectiveness test was conducted by administering pre-test and post-test questions to the students. The results of the video media development research showed a validation level of 86% for the material and 85% for the language, both falling into the very valid category. The product practicality results indicated a practicality level of 91%, also in the very practical category. The effectiveness test yielded a t-value of 16.4.